Eventos adversos musculoesqueléticos reportados durante o treino em esteira em indivíduos com acidente vascular cerebral: uma revisão sistemática - Oliveira, Samara Katiane Rolim de (2020)
ABSTRACT Introduction: Stroke is one of the diseases that most cause disability, leading to impaired gait and important limitations. Treadmill training has been beneficial in the treatment of post-stroke sequelae, largely due to the musculoskeletal effort promoted by the activity. With this, it is possible to assume that some potential risk or injury will occur due to this training. However, adverse events in studies involving treadmill training have not been well reported in the literature. Objectives: To analyze musculoskeletal adverse events reported in trials involving treadmill training for the rehabilitation of a companion who suffered a stroke. Methodology: This study stands out as a systematic review of treatment that practiced treadmill training after a stroke. The search for studies carried out in the databases: MEDLINE Ovid; CINAHL EBSCO; CENTRAL; PsycINFO Ovid; LILACS Bireme; SPORTDiscus EBSCO; PEDro, in the months of October and November 2019, without restriction of publication data, including studies with text available in English. Three independent reviewers evaluated the titles and abstracts from the research; then they assessed the eligibility of the full texts and extracted the relevant data. The outcomes considered were the musculoskeletal adverse events reported in clinical trials. The classification related to musculoskeletal events was performed a posteriori. The data were exposed as characteristics of the included studies, a description of the intervention (treadmill training) and adverse events. Results: The search generated a total of 53,068 studies; after selection, 250 eligible potentials will remain, of which 39 mentioned adverse events in their text, table or graph, with 15 of them reporting musculoskeletal adverse events (taken and / or occurred). Most of the included studies (11) were randomized controlled trials, in which the participants were of both sexes, with strokes of any etiology (60%) and mainly in the chronic phase (80%). In the studies, treadmill training was performed in at least one group (or arm), in isolation or associated with another intervention during training. The pain event was reported in 53% of the studies, and together with the fall event - reported in 40%, were the most reported. Most studies did not classify adverse events according to their severity, and many were not clear that the group belonged to the patients who classify the events. Few studies have reported the use of standardized instruments to assess adverse events. Conclusion: The results show us a need for a more adequate description of adverse events in rehabilitation trials, due to the poor reports on musculoskeletal events. In addition, they indicate that treadmill training can be a source of potential musculoskeletal damage, and with that, the importance of systematic monitoring of musculoskeletal adverse events in future studies on the topic is highlighted.